Current management of migraine in US emergency departments: An analysis of the National Hospital Ambulatory Medical Care Survey*. (April 2015) - Friedman, Benjamin W; West, Jason; Vinson, David R; Minen, Mia T; Restivo, Andrew; Gallagher, E John
Background: Published data from 1998 revealed that most patients treated for migraine in an emergency department received opioids. Over the intervening years, a large body of evidence has emerged demonstrating the efficacy and safety of non-opioid alternatives. Expert opinion during these years has cautioned against use of opioids for migraine. Our objectives were to compare current frequency of use of various medications for acute migraine in US emergency departments with use of these same medications in 1998 and to identify factors independently associated with opioid use. Methods: We analyzed National Hospital Ambulatory Medical Care Survey data from 2010, the most current dataset available. The National Hospital Ambulatory Medical Care Survey is a public dataset collected and distributed by the Centers for Disease Control and Prevention. It is a multi-stage probability sample from randomly selected emergency departments across the country, designed to be representative of all US emergency department visits. We included in our analysis all patients with the ICD9 emergency department discharge diagnosis of migraine. We tabulated frequency of use of specific medications in 2010 and compared these results with the 1998 data. Using a logistic regression model, into which all of the following variables were entered, we explored the independent association between any opioid use in 2010 and sex, age, race/ethnicity, geographic region, type of hospital, triage pain score and history of emergency department use within the previous 12 months. Results: In 2010, there were 1.2 (95% confidence interval 0.9, 1.4) million migraine visits to US emergency departments. Including opioid-containing oral analgesic combinations, opioids were administered in 59% of visits (95% confidence interval 51, 67). The most commonly used parenteral agent, hydromorphone, was used in 25% (95% confidence interval 19, 33) of visits in 2010 versus less than 1% (95% confidence interval 0, 3) in 1998. Conversely, use of meperidine had decreased markedly over the same timeframe. In 2010, it was used in just 7% (95% confidence interval 4, 12) of visits compared to 37% (95% confidence interval 29, 45) in 1998. Metoclopramide, the most commonly used anti-dopaminergic, was administered in 17% (95% confidence interval 12, 23) of visits in 2010 and 3% (95% confidence interval 1, 6) of visits in 1998. Use of any triptan was relatively uncommon in 2010 (7% (95% confidence interval 4, 11) of visits) and in 1998 (10% (95% confidence interval 6, 15) of visits). Of the predictor variables listed above, only emergency department use within the previous 12 months was associated with opioid administration (adjusted odds ratio: 2.87 (95% confidence interval 1.03, 7.97)). Conclusions: In spite of recommendations to the contrary, opioids are still used in more than half of all emergency department visits for migraine. Though use of meperidine has decreased markedly between 1998 and 2010, it has largely been replaced by hydromorphone. Opioid use in migraine visits is independently associated with prior visits to the same emergency department in the previous 12 months.